Rancang Bangun Sistem Informasi Monitoring dan Evaluasi Universal Child Immunization Berbasis Web Pada Dinas Kesehatan Surabaya - Ali, Badar Yasifun; Sulistiowati, Sulistiowati; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Dinas Kesehatan (Dinkes) in Surabaya is a Surabaya city government agencies responsible for public health Surabaya. Surabaya city Health Department has a section which has the task of disaster outbreak that improve family health and prevent and overcome disease. And One of them is with their immunizations to determine immunization coverage or Univesal Child Immunization (UCI) in Dinkes Surabaya. UCI is a condition of achieving complete basic immunization of all infants under one year of age.In carrying out the complete basic immunization program (UCI), the health department of Surabaya city experienced difficulties in implementing the monitoring and evaluation due to the form of presentation that is currently not on time so as to determine the change takes a long time.Based on the above problems, Dinkes Surabaya need information systems that can perform monitoring and evaluation in a timely manner.Based on the results of testing and evaluation, it is known that the information system is made to conduct monitoring and evaluation in a timely manner, so that the Dinkes Surabaya City can immediately take action if it finds that health centers are still in the minimum limit indicator.